2019
DOI: 10.3389/fphy.2019.00003
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Transmission Across Silicon Grain Boundaries by Atomistic Green's Function Method

Abstract: Nanostructured materials are of great interest for many applications because of their special properties. Understanding the effect of grain boundaries on phonon transport in polycrystals is important for engineering nanomaterials with desired thermal transport properties. The phonon transport properties of 3 grain boundaries in silicon are investigated by employing atomistic Green's function method. Results show that similar to electron transport, the perfect grain boundary does not significantly reduce the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The phonon heat transfer coefficients with and without vdW interaction for conduction at contact are respectively 9.19×10 8 and 9.36×10 8 W/m 2 •K. This is in good agreement with prior works [49,56,75] despite the different descriptions of the interatomic force interactions: see the inset of Fig. 2.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The phonon heat transfer coefficients with and without vdW interaction for conduction at contact are respectively 9.19×10 8 and 9.36×10 8 W/m 2 •K. This is in good agreement with prior works [49,56,75] despite the different descriptions of the interatomic force interactions: see the inset of Fig. 2.…”
supporting
confidence: 89%
“…Since this transport mechanism is mediated by lattice vibrations, an all-atom model is the most effective approach for incorporating the three-dimensional (3D) interatomic force interactions into phonon transport calculations. The scattering boundary method and the atomistic Green's function (AGF) framework are both all-atom models that enable calculating transport of coherent phonons inside materials [55,56], across interfaces [57][58][59][60][61], and across vacuum gaps [43-46, 49, 52, 62].…”
mentioning
confidence: 99%
“…( 2). Li et al [62] computed the thermal conductance across silicon GBs with AGF analysis. They found that defective GBs significantly reduced the thermal transport.…”
Section: 𝑹 𝑲 Of Gbs and General Interfaces -Analytical Models Atomist...mentioning
confidence: 99%